2005
DOI: 10.1038/sj.jp.7211275
|View full text |Cite
|
Sign up to set email alerts
|

Management of Birth Asphyxia in Home Deliveries in Rural Gadchiroli: The Effect of Two Types of Birth Attendants and of Resuscitating with Mouth-to-Mouth, Tube-Mask or Bag–Mask

Abstract: OBJECTIVES:To evaluate the effect of home-based neonatal care on birth asphyxia and to compare the effectiveness of two types of workers and three methods of resuscitation in home delivery. STUDY DESIGN:In a field trial of home-based neonatal care in rural Gadchiroli, India, birth asphyxia in home deliveries was managed differently during different phases. Trained traditional birth attendants (TBA) used mouthto-mouth resuscitation in the baseline years (1993 to 1995). Additional village health workers (VHWs) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
94
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 17 publications
1
94
0
Order By: Relevance
“…Neonatal deaths in India AH Baqui et al 6,23,27 The definition used in this study was found to have more than 70% sensitivity and specificity in Bangladesh. 22,25 The proportion of deaths assigned to some causes, particularly sepsis/pneumonia or prematurity, are highly dependent upon their placement within the hierarchy.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Neonatal deaths in India AH Baqui et al 6,23,27 The definition used in this study was found to have more than 70% sensitivity and specificity in Bangladesh. 22,25 The proportion of deaths assigned to some causes, particularly sepsis/pneumonia or prematurity, are highly dependent upon their placement within the hierarchy.…”
Section: Researchmentioning
confidence: 99%
“…Symptoms of respiratory illness are thought to be difficult to elicit from verbal autopsy interviews 20,25,26 and the definition of sepsis or pneumonia used here could include both viral and bacterial infections of various etiologies. Likewise, the definition used for preterm birth ("baby very small or smaller than 6,23,27 The definition used in this study was found to have more than 70% sensitivity and specificity in Bangladesh. 22,25 The proportion of deaths assigned to some causes, particularly sepsis/pneumonia or prematurity, are highly dependent upon their placement within the hierarchy.…”
mentioning
confidence: 99%
“…The remaining 13 references, which pertained to 5 trials, were included in the review. [18][19][20][21][22][23][24][25][26][27][28][29][30] Trial characteristics Table 2 summarizes the characteristics of included trials, all of which were conducted in southern Asian countries with high baseline neonatal mortality rates (> 45 deaths per 1000 live births). Sylhet 18 and Shivgarh 20 trials were cluster-randomized and provided cluster-adjusted mortality data.…”
Section: Trial Flowmentioning
confidence: 99%
“…6 The national neonatology forum of india has defined birth asphyxia as gasping and ineffective breathing or lack of breathing at 1 minute after birth. 7 Neonatal deaths account for 40% of all deaths among children under five among which 80% neonatal deaths are due to prematurity and low-birth-weight, infections, asphyxia and birth trauma. 8 So, by decreasing birth asphyxia related death we can significantly decrease under five mortality.…”
mentioning
confidence: 99%